Well-being, character strengths, and depression in emerging adults - Brito, Almir Diego; Soares, Adriana B. (Frontiers in Psychology, 2023)
Introduction Emerging adulthood is a period of transition between adolescence and adulthood, during which individuals explore different roles and possibilities. This period is often characterized by high levels of stress and uncertainty, which can increase the risk of depression. The aim of this study was to investigate the associations between emerging adulthood dimensions, well-being, character strengths and depression, as well as to verify the differences in the levels of these elements among different groups of depressive symptomatology. Methods Participants were 1,060 individuals (741 females, 305 males) between the ages of 18 and 30 years (M = 22.3, SD = 3.72). Spearman’s correlation, linear regression, and Kruskal- Wallis with pairwise post-hoc analyses were used to analyze the data. Results There were significant positive correlations between emerging adulthood dimensions, well-being, and character strengths, and negative correlations between these variables and depression. There were also significant differences in the means of the evaluated constructs among the symptomm groups. Discussion The findings suggest that emerging adulthood dimensions, well-being, and character strengths are all associated with depression in emerging adults and have important implications for the provision of interventions in health and education for emerging adults. The study provides a deeper understanding of the factors influencing depression during emerging adulthood and emphasize the importance of promoting positive psychology elements and developing personalized interventions for emerging adults. This also suggest that public policies related to mental health and education should take into account the unique needs of emerging adults.